The Role Of Parents In Learning At Home During The Covid-19 Pandemic - Meidawati Suswandari (AL-ISHLAH: Jurnal Pendidikan, 2022)
During the pandemic until now, the role of parents plays the most important role in the development of children's learning. Moreover, working while teaching children at home as a substitute for honorary teachers while studying from home. The purpose of this study was to describe and analyze the role of today's parents in the learning process of children during the COVID-19 pandemic in Palur Village, Sukoharjo. This research use desciptive qualitative approach. The research informants were 4 parents in Palur Village, Sukoharjo. The data was collected by interview, documentation study, and literature study. Then analyzed using data reduction, data presentation, and drawing conclusions. The data obtained were tested for validity using triangulation of data sources and techniques. The findings show that the current role of parents in the context of the millennial era, especially during the COVID-19 pandemic, must be smart and clever in harmonizing existing conditions. Because the main factor in family education is parents, especially in growing and developing parenting patterns and educating children to become parents. Some of the difficulties experienced by parents in accompanying children to study at home during the Covid-19 pandemic are the lack of understanding of the material by parents, the difficulty of parents in fostering children's learning interests, not having enough time to accompany children because they have to take care of the house, their children who others, working to open an online shop, and the impatient attitude of parents in accompanying their children while studying at home..